Mining (Australia) - Topal, Erkan; Mather, D. (Berkshire Publishing Group, Great Barrington, 2012)
Sustainably managed mining is based on three dynamic control factors—sociopolitical, techno-environmental, and techno-economic—that drive innovation and engineering toward cheaper and more efficient solutions. In Australia, high productivity and the ability to mine lower grades in harsher environments have led to an increase in mining waste as the commodity demand increases. More stringent social and environmental protection measures, however, will advance responsible and efficient mining.